Taxonomic reassessment of Calamagrostis garhwalensis (Poaceae: Agrostidinae) - Paszko, Beata (Phytotaxa, 2014)
Calamagrostis garhwalensis (Poaceae: Agrostidinae) described from northwestern India has been taxonomically controversial. The distinctiveness of this enigmatic and uncommon species is assessed and its taxonomic status partly clarified. Putative relationships among C. garhwalensis and its close relatives from northwestern India, such as C. emodensis, C. gamblei, C. stolizkai and the C. pseudophragmites complex are characterized with a morphometric analysis. The presence of rachilla extensions has been overstated as a diagnostic characteristic for C. garhwalensis. Specimens other than the type previously designated as C. garhwalensis belong in other species. New records of C. garhwalensis are reported from northwestern India and southwestern China.